Oligocene clockwise rotations along the eastern Pamir: Tectonic and paleogeographic implications. Issue 2 (15th February 2014) - Bosboom, Roderic; Dupont‐Nivet, Guillaume; Huang, Wentao; Yang, Wei; Guo, ZhaoJie
Abstract Despite the importance of the Pamir range in controlling Asian paleoenvironments and land‐sea paleogeography, its tectonic evolution remains poorly constrained in time and space, hindering its potential for understanding deep to surface processes. We provide here new constraints on vertical‐axis tectonic rotations from the southwest Tarim Basin along the eastern flank of the Pamir arcuate range based on paleomagnetic results. Two well‐dated Eocene to Oligocene sections, previously analyzed using biostratigraphy and magnetostratigraphy, yield consistently clockwise rotations of 21.6 ± 4.2° in 41 to 36 Ma strata then 17.1 ± 6.5° in 33 to 28 Ma strata at the Aertashi section and 14.2 ± 11.5° in 41 to 40 Ma strata at the Kezi section. Combined with a regional review of existing paleomagnetic studies, these results indicate that most of the clockwise rotations along the eastern Pamir occurred during Oligocene times and did not extend systematically and regionally into the Tarim Basin. In contrast, on the western flank of the Pamir tectonic rotations in Cretaceous to Neogene strata are regionally extensive and systematically counterclockwise throughout the Afghan‐Tajik Basin. This timing and pattern of rotations is consistent with paleogeographic reconstructions of the regional sea retreat out of Central Asia and supports a two‐stage kinematic model: (1) symmetric rotations of either flanks of the Pamir arcuate range until Oligocene times followed by (2) continued rotations on its western flank associated with radial thrusting and, along the eastern flank, no further rotations due to decoupled transfer slip starting in the Early Miocene.